BIROKRASI, KORUPSI, DAN KEKUASAAN - Haboddin, Muhtar -; Rozuli, Ahmad Imron (Faculty of Social and Political Science Universitas Brawijaya, 2017)
This study explains about bureaucracy, corruption, and power. Bureaucracy is an institution that has huge power in governance. Such power deals with public interest, and potentially it can also be abused. One of power abuses in bureaucracy is corruption. Both bureaucracy and corruption are huge problem that needs to be solved. If bureaucracy corrupts, it will impacts to bad public service, bad government performance, and disadvantaged people. In reducing of power abuse in bureaucracy, political and civil society controls are needed. The control is very needed for guiding bureaucrat behavior in doing job and function.